Eficacia de la Rehabilitación Precoz para reducir el Nivel de Dependencia en Pacientes con Fractura de Cadera del Hospital Víctor Lazarte Echegaray - Rubio Rubio, Erika Geraldine (2022)
Hip fractures are an important health problem in the elderly population. Currently, hip fractures affect 18% of women and 6% of men globally. Epidemiological studies have shown that the incidence of hip fractures increased from 1986 to 1995, but then steadily decreased until 2012. From 2012 to 2015, the incidence of hip fractures reached a plateau. In Peru, it is estimated that 12-16% of Peruvian women over 50 years of age will suffer a hip fracture per year. Since they are mostly elderly patients, the presence of neurological and medical disorders must be ruled out before surgery, adopting the appropriate measures. A detailed evaluation is essential to minimize complications, such as muscle weakness and pressure ulcers. The application of an integrated rehabilitation program after hip fracture surgery is essential in elderly patients, and programs of this type have recently been established in several countries. The objective of the rehabilitation of patients in the acute and subacute phases is to get them out of bed as soon as possible and to get them to stand and walk with technical aids. At this stage, it is necessary to recover joint range of motion and strength, control pain and training in activities of daily living. To assess competence in activities of daily living, the KATZ index can be used, tests should also be performed to screen for cognitive dysfunction and dementia and that it is common for patients to have comorbidities such as Alzheimer's dementia. In this way, as a comprehensive treatment is needed, there is a growing interest in the development of standardized protocols through team and multidisciplinary approaches.